2017
DOI: 10.1021/acs.est.7b00736
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Alterations in Pseudomonas putida F1 Exposed to Nanoscale Zerovalent Iron: Effects of Short-Term and Repetitive nZVI Exposure

Abstract: In this study, we report the effect of the commercial nanoscale zerovalent iron (nZVI) on environmental bacteria, emphasizing the importance of nZVI-bacterial membrane interaction on nZVI toxicity as well as the adaptability of bacteria to nZVI. Exposure of Pseudomonas putida F1 to 0.1, 1.0, and 5.0 g/L of nZVI caused the reduction in colony forming units (CFUs) substantially for almost 3 orders of magnitude. However, a rebound in the cell number was observed after the prolonged exposure except for 5.0 g/L nZV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 85 publications
(152 reference statements)
3
29
0
1
Order By: Relevance
“…3 and 4). Type I represents OTUs with enhanced adaptation over TiO 2 NP dosing frequencies that showed a successive increase in relative abundance, which is similar with the reported response of Pseudomonas putida F1 to repeated exposure of nanoscale zerovalent iron (nZVI) (Kotchaplai et al, 2017). In return, the established persistent phenotypes (through acclimation, detoxification enzymes, and horizontal transfer of resistant genes) will lead to the promotion of the resistant taxa and the associated functions (Ernst et al, 2016).…”
Section: Dynamics In Soil Bacterial Community During the Repeated Expsupporting
confidence: 61%
See 1 more Smart Citation
“…3 and 4). Type I represents OTUs with enhanced adaptation over TiO 2 NP dosing frequencies that showed a successive increase in relative abundance, which is similar with the reported response of Pseudomonas putida F1 to repeated exposure of nanoscale zerovalent iron (nZVI) (Kotchaplai et al, 2017). In return, the established persistent phenotypes (through acclimation, detoxification enzymes, and horizontal transfer of resistant genes) will lead to the promotion of the resistant taxa and the associated functions (Ernst et al, 2016).…”
Section: Dynamics In Soil Bacterial Community During the Repeated Expsupporting
confidence: 61%
“…For example, a tolerant bacterium (Rhodanobacter sp.) emerged in soils exposed to silver nanoparticles (Samarajeewa et al, 2019), and a persistent phenotype of Pseudomonas putida F1 with a more rigid membrane and higher tolerance was detected after several re-dosing cycle of nanoscale zerovalent iron (Kotchaplai et al, 2017). In contrast, for ammonia-oxidizing bacteria, the repetitive dosing of TiO 2 NPs was found to be more harmful than one-time exposure (Simonin et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…38 Other studies investigating nanoparticle adaptations have shown clear bacterial response but have not demonstrated a stable nanoparticle resistance phenotype. 41,48,[66][67][68][69] Due to the ability of S. oneidensis MR-1 to continue replication under increasing concentrations of NMC, the heritability and stability of the adaptation aer the pressure has been removed, and the presence of a nanoparticle-specic impact, it is rational to consider this resistance and not simply tolerance. 37,38,49,65 Microbial resistance is important to consider when addressing the regulation of soluble nanomaterials.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the degree of cis to trans conversion correlates with the toxicity/hydrophobicity and the concentration of toxic organic hydrocarbons but does not depend on a distinctive chemical structure of the stressor (Heipieper et al 1995 ; Neumann et al 2005 ). Besides various toxic organic compounds, osmotic stress, the presence of heavy metals, and antibiotics acting on the membrane result in an increase of the trans / cis ratio (Hachicho et al 2014 ; Heipieper et al 1996 ; Isken et al 1997 ; Kotchaplai et al 2017 ; Piotrowska et al 2016 ). This reflects the importance of the system as general stress response mechanism in Gram-negative bacteria (Ramos et al 2001 ; Segura et al 1999 ; Zhang and Rock 2008 ).…”
Section: Cis-trans -Isomerization Of Membrane Fatty Acidsmentioning
confidence: 99%